Radiocarbon dating minute amounts of bone (3–60 mg) with ECHoMICADAS - Cersoy, S. (Sci Rep, 2017)
Because hard tissues can be radiocarbon dated, they are key to establishing the archaeological chronologies, palaeoenvironmental reconstructions and historical-biogeographical processes of the last 50,000 years. The advent of accelerator mass spectrometers (AMS) has revolutionized the field of archaeology but routine AMS dating still requires 60–200 mg of bone, which far exceeds that of small vertebrates or remains which hold a patrimonial value (e.g. hominid remains or worked bone artefacts). Here, we present the first radiocarbon dates obtained from minute amounts of bone (3–60 mg) using a MIni CArbon DAting System (MICADAS). An optimized protocol allowed us to extract enough material to produce between 0.2 and 1.0 mg of carbon for graphite targets. Our approach was tested on known-age samples dating back to 40,000 BP, and served as proof of concept. The method was then applied to two archaeological sites where reliable dates were obtained from the single bones of small mammals. These results open the way for the routine dating of small or key bone samples.